Alex Street Band - Alex Street Band; Ellala, Tea; Junttila, Pietari; Junttila, Tuomas; Kiviluoto, Samu; Lindgren, Heikki; Lindqvist, Jarkko; Myllymäki, Timo; Palomäki, Kalle; Pentikäinen, Matti; Raittinen, Saara; Toivanen, Kyösti; et al. (Alex Street Band, 1999)
9 kappaletta.